Malaysian firms cost of equity: systematic versus downside risk - Swee Sim, F.; Kim Leng, G. (2009)
Of late, concerns are raised against the application of the classical one-factor CAPM in emerging markets. Adopting some of the emerging market models reviewed in Pereiro (2001), together with the two-factor CAPM models proposed in this study, we make comparison between systematic and downside risk measures to estimate the cost of equity of Malaysian firms over 2000-2007. Overall, our results are consistent with Estrada (2000, 2001)’s findings which support downside risk measures over standard risk measures. Based on standard model selection criteria we find that two-factor downside betas have the highest explanatory power on actual stock returns, compared to single-factor models that consider only either local or global risk factor. The cost of equity for Malaysian firms calculated based on the two-factor downside betas have an average value of 11.42%. The Adjusted Local CAPM (ALCAPM) gives an average cost of equity value of 10.34%. If Malaysian investors have used the ALCAPM, they would have underestimated the firm’s cost of equity by an average of 108 basis points.